The Obedience Factors of Teenage Girls to Consume Iron Tablet at SMK Negeri 1 Kedawung, Cirebon - Hilda Novita; Neli Nurlina; Suratmi Suratmi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
The government gives society Fe tablets as a way to handle anemia in Indonesia. The low obedience to consume Fe table is the cause of this program that is not effective enough from the government. The research aim is to know the correlated between knowledge, teachers' support, parents' support, health workers' support and self-efficacy on teenage girls’ obedience to consume Fe tablets. The research was an observational study by using a cross-sectional design for 191 students who were taken by purposive sampling technique. Collecting data used questioners that have been tested for validity and reliability. Then, the data were analyzed by using chi-square test and mann withney. The results of the analysis showed that the majority of teenage girls have good knowledge of the importance to consume Fe tablets, namely (52.4%), teachers support (68.8%), parents support (56.0%), health workers support (60.2%), positive self-efficacy (59.2%) and level of compliance with consuming Fe tablets 25% (1 tablet/month) (73.8%). The results of statistical analysis of teenage girls’ as factors in consuming Fe tablets are as follows: a knowledge factor (p-value 0.033), teachers support (p-value 0.008), parents support (p-value 0.011), health workers support (p-value 0.004) and self-efficacy (p-value 0.000). There was a correlated between knowledge, teachers' support, parents' support, health workers' and self-efficacy on teenage girls’ obedience to consume Fe tablets. The suggestions for midwives or other health workers by increasing cooperation to monitor and route outreach to each school either through printed media such as leaflets, books or other more creative electronic media.